HUBUNGAN SOSIAL PEKERJA WANITA DI PERKEBUNAN KELAPA SAWIT DI DESA SIMPANG PERAK JAYA KECAMATAN KERINCI KANAN KABUPATEN SIAK - Sri Desrianti; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The aim of this research is to analyze social relationship of palm plantation’s female workers and to find out the working system of female workers in palm plantation in Desa Simpang Perak Jaya Kecamatan Kerinci Kanan Kabupaten Siak.Population of this research is all palm plantation’s female workers in Desa Simpang Perak Jaya. The number is 80 people. 50% of them or 40 people become the sample. Sampling technique was done by simple randlom sampling technique.Result shows that interaction is highly needed in creating social relationship among personals or groups. In palm plantation in Desa Simpang Perak Jaya Kecamatan Kerinci Kanan Kabupaten Siak, the society members can be called as heterogen society. We can find some different etnics like Minang, Melayu, Jawa, Sunda, Batak, and Nias. Relationship found among female workers is based on the same interest, which is to work together and to help each other in work and life.Keyword: Social Relationship, Female Worker, Palm Plantation